Bio-inspired drug delivery systems: an emerging platform for targeted cancer therapy. (22nd March 2018) - Ngandeu Neubi, Gella Maelys; Opoku-Damoah, Yaw; Gu, Xiaochen; Han, Yue; Zhou, Jianping; Ding, Yang
Abstract : Bio-inspired platforms directly derived from biological sources are becoming a rapidly emerging field in the development of future anticancer therapeutics. The various platforms discussed are bacteria-based, virus-inspired, cell-derived, nanostructured lipid nanoparticles, and biomacromolecular drug delivery systems. Abstract : The quest for an ideal cancer treatment has led to the exploration of a variety of platforms to facilitate highly desirable and efficient drug delivery. As most anticancer drugs possess therapeutic potency to destroy tumor cells, there is a need to steer the compounds to their required sites using site-specific drug delivery vehicles. This has inspired the investigation of various natural particulates and biomaterials for the purpose. Bio-inspired platforms that directly mimic natural components in the body have demonstrated their ability to serve as one of the most versatile and innovative drug delivery systems in cancer therapy and diagnosis. The primary advantage of this innovation lies in the fundamental changes in systemic biodistribution that non-native drug delivery does not possess. This review will try to provide a comprehensive understanding and a succinct evaluation of various intelligent bio-inspired delivery platforms, which have become prominent in recent studies. Recent innovative examples and their advantages and limitations as well as future clinical potential will also be thoroughly discussed.